ANALISIS BIAYA PRODUKSI DAN PERHITUNGAN TARIF AIR MINUM PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KABUPATEN LOMBOK TIMUR - Ilma Nopita Sari; Herlina Pusparini; Nurabiah Nurabiah (Universitas Dharmawangsa, 2023)
The study aims to determine the determine the calculation of production costs and water tariffs at the Regional Drinking Water Companies (PDAM) of East Lombok Regency. The calculation of production costs uses the calculation of raw material costs, labor costs, and factory overhead costs, and the calculation of new water tariffs based on PERMENDAGRI Number 21 of 2020 to achieve the principle of full cost recovery. This research uses a quantitative descriptive method with primary data sources obtained through documentation. The results and discussion show that when calculating the production costs of PDAM Lombok Regency, the amount is in accordance with the results of the research. However, it must still divide the production cost components, and the cost structure at the PDAM only uses water source costs, water treatment costs and factory overhead costs. The calculation of the current PDAM tariff with the Â researcherâ€™s calculation based on PERMENDAGRI Number 21 of 2020, where there is a significant difference and can result in losses to consumers who use the PDAM